Identification of 16p11.2 deletion syndrome on a child inpatient psychiatric unit: A case report and call for inpatient genetic testing. Issue 2 (2nd January 2021) - Gibbs, William; Bell, Harrison; Ajith, Aniruddh; Sadtler, Kim; Escuro, Katrina; Brooks, Deborah; Edwards, Sarah
Abstract: Purpose: This case highlights the importance of nursing‐directed interprofessional treatment and inpatient unit genetic testing to identify genetic syndromes that may potentiate psychiatric conditions. Sources Used: A case study of a 10‐year‐old Caucasian male with a history of a congenital heart defect, hand malformation, and low academic functioning who was admitted to the child inpatient psychiatric unit for eloping from school, aggression, and possible psychotic symptoms. Data were collected using patient medical records and interprofessional evaluation from nursing, psychiatry, and occupational therapy. Results: The patient was treated with risperidone to manage psychotic symptoms. Dietary, occupational therapy, and scholastic plans were also implemented. After discharge, results of genetic microarray analysis revealed a Type 1 16p11.2 deletion. Conclusion: The role of nursing, interprofessional collaboration, and access to consultation teams play a crucial role in patient care for early diagnosis and treatment. Inpatient genetic testing has the potential to quickly identify and diagnose previously unidentified symptom clusters, leading to early intervention, closer monitoring, and improved patient outcomes.